Uso da metodologia Canvas para o planejamento e desenvolvimento de novos negócios - Lopes, Tobias da Silveira (2015)
The need for constant renewal organizations undertake to remain at the forefront of the dynamic demands of the market and society as well as the indispensable quest for expansion and business development have required practical approaches to foster creativity and to enable change, given that established processes to manage such objectives are not easily identified. By doing so, this organizational model facilitates the re-assessment the scope and proposal of each organization as a pathway to reinvention. Among numerous approaches, the Canvas method has been utilized by organizations with different sizes and backgrounds. It is presented as a model of renowned efficiency as it proposes not only structure but also a means to foment creative thinking, collaborative work, and the organization and its relationships as a whole. This study is aimed at the examination of the use of the Canvas methodology in promoting organizational planning and development within a managerial group focused on the service industry, food and trade. It takes into consideration concepts drawn from the literature regarding the perception of business professionals about the Canvas method and its application in aforementioned organizational context. This qualitative research study relied on observation and descriptive narrative and data derived from the review of documents and from interviews of managers and the consultant involved in the implementation of the methodology. The conclusion reveals that the implementation of the Canvas was successful as it made use of the original proposal developed by Professor Alexander Osterwalder. It also reveals that the successful implementation is the result of the strong entrepreneurship culture of the managers, of the advanced level of organizational maturity, of the favorable conjuncture, and of the approach with which the managers absorbed the methodology as a mental model.